Kemampuan koneksi matematis berdasarkan disposisi matematis siswa pada materi sistem persamaan linear dua variabel - Ersa Siti Fatimah; Rostina Sundayana (Institut Pendidikan Indonesia, 2022)
The reality on the ground shows that students' ability to make mathematical connections is still relatively low. The purpose of this study was to determine the ability of mathematical connections based on the mathematical disposition of students on the material of a two-variable linear equation system in Jayaraga village. The population in this study were students of SMP/MTs equivalent in Jayaraga village, while the sample was selected based on a purposive sampling technique of 3 students. The analysis of the results of this study shows that the mathematical connection ability and mathematical disposition: (1) The students' mathematical connection ability and mathematical disposition are in the medium category. (2) The level of mathematical disposition ability tends to affect the level of students' mathematical connection abilities. Students who have a high level of mathematical disposition ability tend to have better mathematical connection abilities. Students who have a moderate level of mathematical disposition ability tend to have ordinary mathematical connection abilities. And students who have a low level of mathematical disposition skills tend to have low mathematical connection abilities. Kenyataan di lapangan menunjukkan bahwa kemampuan siswa dalam melakukan koneksi matematis masih tergolong rendah. Tujuan penelitian ini adalah untuk mengetahui kemampuan koneksi matematis berdasarkan disposisi matematik siswa pada materi sistem persamaan linear dua variabel di desa Jayaraga. Populasi dalam penelitian ini adalah siswa SMP/MTs sederajat yang berada di desa jayaraga, sedangkan sampel dipilih berdasarkan teknik purposive sampling sebanyak 3 orang siswa. Analisis hasil penelitian ini menunjukkan bahwa kemampuan koneksi matematis dan disposisi matematik: (1) Kemampuan koneksi matematis dan disposisi matematik siswa masing-masing termasuk ke dalam kategori sedang. (2) Tingkat kemampuan disposisi matematik cenderung mempengaruhi tingkat kemampuan koneksi matematis siswa. Siswa yang memiliki kemampuan disposisi matematik tingkat kategori tinggi cenderung memiliki kemampuan koneksi matematis lebih baik. Siswa yang memiliki kemampuan disposisi matematik tingkat kategori sedang cenderung memiliki kemampuan koneksi matematis yang biasa. Dan siswa yang memiliki kemampuan disposisi matematik tingkat kategori rendah cenderung memiliki kemampuan koneksi matematis yang rendah.